Knowledge management in the supply chain management case: schneider-electric (2013)
Abstract. Nowadays, with outsourcing, companies have started to seek external skills, competences and knowledge to provide value. Thus to survive, enterprises must maintain and use internal and external knowledge. This study focuses in outsourcing of professional service in Schneider Electric, a French enterprise. By means of a purchasing process, this study examines the relationships between the buyers, intern clients and suppliers during the development of six projects, in order to determinate the knowledge use as an internal and external source applying the knowledge chain model. We interviewed eighteen people directly involved. We found that knowledge management can be used as an effective collaboration tool and that it is one of the best practices that positively influence the supply chain relationship. Implications for future research and practice are offered.